Gamma-ray attenuation coefficients of carbon steel plates using iridium-192 / Siti Madiha Muhammad Amir - Siti Madiha, Muhammad Amir (2012)
Measurement of gamma radiation attenuation coefficients on carbon steel using gamma radiation beam from Iridium-192 has been made to permit their use for precision measurement, material studies and in various industrial radiographic techniques. The material examined is carbon steel plates with various thicknesses ranging from 2 mm to 13 mm. There are two aspects in this study; determination of the attenuation coefficient using theoretical method, and from experiments. Two types of detectors are used; the film radiography and ion chamber. The gamma ray source is the polychromatic radionuclide Iridium-192. Cross section of the incoherent scattering of every element in the carbon steel material sample has been calculated using the Klein-Nishina formula incorporating the structure function correction. We integrate the Klein-Nishina formula using the Gauss-Legendre quadrature and the cross section agrees very well with the published results. The cross section of the incoherent scattering is used to calculate the theoretical effective linear attenuation coefficient and is found to be 0.231. The effective linear attenuation coefficient value from the two experiments has the value of 0.3401cm−1mm− as determined from the transmission curves which is consistent with the theoretical value.